กลยุทธ์การบริหารวิชาการโรงเรียนมัธยมศึกษาตามแนวคิดสมรรถนะภาวะผู้นำเชิงผู้ประกอบการ - อิฏฐิรา ทรงกิติพิศาล (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This research aimed to 1) study the conceptual framework of academic management in secondary schools and the concept of entrepreneurial leadership competencies; 2) study the levels of entrepreneurial leadership competencies of secondary school students; 3) analyze strengths, weaknesses, opportunities, and threats of academic management in secondary schools based on the concept of entrepreneurial leadership competencies; and 4) develop academic management strategies in secondary schools based on  the concept of entrepreneurial leadership competencies. Multi – phase mixed method design research was used. The quantitative and qualitative data was collected altogether. The samples included 341 secondary schools under Office of the Basic Education Commission. The informants included school executives, curriculum supervisor, teachers, and students. The instruments included the questionnaire and the assessment form. The statistics for data analysis included frequency, percentage, mean, SD, PNImodified, and content analysis from the focus group. The findings revealed that 1) the conceptual framework of academic management in secondary schools included 4 jobs, i.e, (1) curriculum development; (2) instruction management and extra-curricular activity management; (3) measurement and evaluation; and (4) the development of media, innovation, technology for education, and learning sources. For the concept of entrepreneurial leadership competencies, it included 3 core competencies and 11 sub-competencies as follows. (1) relational-oriented competencies included 4 sub-competencies, i.e., having ethics and integrity, having emotional intelligence and personal mastery, having a global mindset, and being an effective bargainer. (2) Task-oriented competencies included 4 sub-competencies, i.e., innovativeness, having intellectual versatility, improvement-oriented, and organizational savvy. And (3) scenario enactment competencies included 3 sub-competencies, i.e.,ability to identify and articulate a vision, proactiveness, and risk taking. 2) For the levels of entrepreneurial leadership competencies of secondary school students, it was found that the mean of relational-oriented competencies was highest, for the sub-competency of "having a global mindset." The mean of scenario enactment competencies was lowest, for the sub-competency of "ability to identify and articulate a vision." 3) The strength of academic management in secondary schools based on the concept of entrepreneurial leadership competencies was instruction management and extra-curricular activity management. The weaknesses included curriculum development; measurement and evaluation; and the development of media, innovation, technology for education, and learning sources. The opportunity was technological state. Threats included political state, government policies, economic state, and social state. 3) Academic management strategies in secondary schools based on the concept of entrepreneurial leadership competencies included 4 key strategies. (1) Make over the course of creating entrepreneurial leadership competencies included 2 minor strategies. (2) Drive instruction management and manage an extra-curricular activity for creating entrepreneurial leadership competencies included 2 minor strategies. (3) Make over measurement and evaluation of creating entrepreneurial leadership competencies included 2 minor strategies. And (4) Make over the development of media, innovation, technology for education, and learning sources for creating entrepreneurial leadership competencies included 2 minor strategies.